2012
DOI: 10.4028/www.scientific.net/amr.450-451.749
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Mechanical Properties of Bamboo’s Joints under Tension and Compression Load

Abstract: The sleeve-bolt connection and the groove-plate connection are two major forms of bamboo’s joints under tension and compression load, and the strength of these two connections is normally governed by the brittle failure mode of shearing-split. A new configuration of sleeve-cement bamboo joint is designed. Comparative loading tests were carried out to study the static tensile and compressive performances of the bamboo joints. It is found that the joint with sleeve-cement connection behaves more ductile under te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Fu et al [73] developed a novel sleeve-cement bamboo joint configuration, utilizing steel sleeves, rings, and mortar for adhesive purposes. They also investigated the performance of sleeve-bolt and groove-plate connections, finding that these joints exhibit brittleness under axial load, with the failure mode being governed by shearing-split.…”
Section: Codes and Standards For Bamboomentioning
confidence: 99%
“…Fu et al [73] developed a novel sleeve-cement bamboo joint configuration, utilizing steel sleeves, rings, and mortar for adhesive purposes. They also investigated the performance of sleeve-bolt and groove-plate connections, finding that these joints exhibit brittleness under axial load, with the failure mode being governed by shearing-split.…”
Section: Codes and Standards For Bamboomentioning
confidence: 99%
“…The corresponding experiments showed that this connection could effectively improve the load-bearing capacity of connections, and their bearing capacities were related to the strength of the embedded wood. Fu et al [10] put the steel sleeve into the bamboo tube, then injected the mortar between the sleeve and the bamboo inner wall, and finally used steel hoops to reinforce the end of the bamboo tube. Their tensile and compression tests showed that this connection had the good ductility and high load-carrying capacities, and could effectively transfer axial load.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al [18] proposed a sleeve-cement butt joint, in which the internal wall of the bamboo cavity was roughened, the steel sleeve embedded in the bamboo cavity was perforated and fixed with pin, the cement mortar was injected between the sleeve and the bamboo tube, and the outer surface of the bamboo tube was laterally restrained by a steel ring. The connection strength was provided by the friction force between the mortar and internal wall of the bamboo and the mechanical bite force between the mortar and sleeve.…”
Section: Introductionmentioning
confidence: 99%